Pengaruh Berkumur Air Kelapa (Cocos nucifera) terhadap Laju Aliran Saliva (e-GiGi, 2024)
Abstract: Decreased salivary flow rate can be caused by many things, inter alia age, consumption of certain drugs, and psychological effects. The benefits of coconut water have been widely studied, one of which is related to dental and oral health. However, there are still not many studies about the effects of various varieties of coconut water in increasing the flow rate of saliva, especially old coconut water which is often thrown away as waste. This study aimed to determine whether there was an effect of coconut water (Cocos nucifera) gargling on the rate of salivary flow. This was an experimental and analytical study with a quasi-experimental design, and pre-test and post-test control group design approaches. Samples were dentistry undergraduate students of Universitas Sam Ratulangi taken by simple random sampling. Samples were divided into two groups: treatment group (gargling with old coconut water) and control group (gargling with mineral water). The results showed that in the treatment group, there was an increase of salivary flow rate from 0.7114 to 1.1248 after gargling with old coconut water. Meanwhile, in the control group, there was an increase of salivary flow rate from 0.7962 to 0,8495 after gargling with mineral water. Since research data were normally distributed and homogenous, the statistical analysis was continued with the unpaired T-test which obtained a p-value of